Government Policies and Quality Care in a Mental Health Center from the Perspective of the LTGBIQ+ Community 2023 - Reyes Castillo, Eduardo Antonio (2024)
The purpose of this research was to evaluate how government policies affect quality care in a mental health center according to the perspective of the LTGBIQ+ community in the year 2023. An applied quantitative approach was used with a non-experimental correlational design. The sample was made up of 200 people of diverse sexual orientation and gender identity from the province of Trujillo. The instruments used were validated by experts, and after a pilot test, high reliability of the instrument was obtained. As a conclusion of the work, a depen- dency between the variables was discovered. Therefore, it is accepted that the implementation of government policies influences quality care directed toward LTGBIQ+ people.